Hepatitis A Virus among Drug Users and the Role of Vaccination: A Review - Lugoboni, Fabio; Pajusco, Benedetta; Albiero, Anna; Quaglio, Gianluca (Frontiers in Psychiatry, 2012)
In countries with advanced economies better health and hygiene conditions, along with the introduction, in some cases, of global vaccination, have relegated most viral hepatitis to marginal social groups and, in particular, drug users (DUs). The availability of safe and effective vaccines for hepatitis A virus (HAV) and B (HBV) may play a major role in combating this phenomenon. Despite the availability of a safe and effective vaccine for over a decade and the recommendations of international health organizations, vaccinations against HAV among DUs are not as widely known and available as are HBV vaccinations. The purpose of this review article is to present the most significant data in the literature on the prevalence of HAV among DUs and the role of targeted vaccination. To our knowledge, the present article is the first to solely deal with vaccination against HAV in DUs. Immunization after the administration of anti-HAV vaccine has been demonstrated in DUs even if they have responded significantly less than either the GPOP or carriers of chronic liver disease. All the vaccines were well tolerated and adherence to the vaccine schedule was good. Further studies are needed to optimize the timing and doses of vaccine to be administered to DUs, especially to assess adherence and antibody persistence. Vaccination campaigns are feasible among DUs and have proven to be highly cost-effective.